Digitalization of Marketing Education: New Approaches for Universities in the Post-Covid-19 Era - Samet Aydın; Sahure Gonca Telli (Üniversite Araştırmaları Dergisi)
Education is one of the areas most affected by the transition to the information age. Universities and faculties/schools have to adapt to this, otherwise the consumption of information that is increased and shared from different environments may be detached from universities. Marketing education, of course, gets its share from these developments. In this direction, a descriptive study was conducted on how to follow marketing science and education in this new situation. This study focuses on digital disruptions in education and the effects of the deterioration caused by digitalization on marketing education. Moreover, the new approaches which are appropriate for the mandatory change in marketing education with reasons and recommendations are discussed. In the information age, educational institutions have to adapt to these new situations and new norms. Therefore, concepts such as active, adaptive and experiential learning with addition of new tools should be included in marketing education.